Contradiction of Power Within Muslim Women in Minangkabau Matrilineal Society - Alam, Lukis; Muhammad, Atha Mahdi (Pascasarjana IAIN Pontianak, 2024)
This research explores the relationship between power and gender, focusing mainly on Minangkabau Muslim women. The study integrates a literature review with ethnographic methods to understand how these women navigate societal structures that prioritize male authority, commonly referred to as ‘patriarchal frameworks ‘, while adhering to cultural traditions. Data were collected from academic sources, community reports, and fieldwork, highlighting women’s lived experiences in key lineage and household leadership positions. The findings indicate that while Minangkabau Muslim women are empowered by their roles as lineage bearers and heads of households, they encounter significant challenges due to the intersection of gender and Islamic norms. Tensions emerge between their matrilineal heritage and the patriarchal structures reinforced by specific interpretations of Islam, which restrict their economic participation, decision-making power, and access to resources. Despite these constraints, women utilize strategies such as pursuing financial independence, engaging in education, and reinterpreting Islamic teachings to align with their cultural and gender identities. This research emphasizes the complexities of gender dynamics in matrilineal societies, especially where Islamic norms intersect with local traditions. It highlights the importance of evolving cultural practices in fostering more inclusive and equitable social structures, offering a potential pathway for positive change within the Minangkabau community.